Correlation Realignment Mechanical Tibiofemoral Angle With Clinical Outcome On Patients Knee Osteoarthritis Valgus Deformity Perforemed Total Knee Arthroplasty at prof. Dr. R. Soeharso Orthopaedic Hospital Surakarta - Warman, Fanny Indra; Islami, Umar Kharisma; Utomo1, Pamudji; Anwar, Iwan Budiwan; Sibarani, Tangkas SMHS (Indonesian Hip and Knee Society (IHKS), 2022)
Knee osteoarthritis (OA) are the most important because of the high prevalence of pain and disability in older adults. Angular deformities around the knee joint necessitate special consideration to restore normal alignment during TKA. In the region of 10–15% of patients requiring a primary TKA present with a valgus deformity (VD), the accurate correction of which still poses a challenge. In Ranawat grade-III the axis deviation is more than 20°. The aim of this research to savy correlation realignment mechanical tibiofemoral angle with clinical outcome on patients knee osteoarthritis valgus deformity performed TKA with non-constrained imlpant. This research is an analytics observational with cross sectional that group patients knee osteoarthritis valgus deformity underwent total knee arthroplasty and performed correlation realignment tibiofemoral angle as well as clinical outome with total sampling method on patients knee osteoarthritis valgus deformity Kellgren Lawrence grade III–IV, have radiological knee x-ray and lower extremity scanogram underwent TKA one side by orthopaedic surgeon sub adult reconstruction. Evaluation has performed to pain scale used Visual Analog Scale (VAS) score, clinical outcome with Knee Society Score (KSS), realigment mechanical tibiofemoral angle before and after TKA. Data were analyzed using t-test and correlation test with SPSS version 16. The result with analyzed 28 (male 6, female 22) patients with a mean age 65,75 years, which divided into three group Ranawat grade I was 14 patients, grade II was 9 patients and III was 5 patients. They were evaluated for VAS score, KSS objective and functional, mechanical tibiofemoral angle have significant result (P 0,05). There was also significantly correlation between improvement mechanical tibiofemoral angle with KSS knee score based value (P 0,05). In this study we found that TKA with non-constrained implant on knee osteoarthrits valgus deformity provides significant result in reducing pain scale and increased clinical outome.